2023
DOI: 10.1073/pnas.2304306120
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite nanoparticle coating chemistry regulates root uptake pathways and iron chlorosis in plants

Abstract: Understanding the fundamental interaction of nanoparticles at plant interfaces is critical for reaching field-scale applications of nanotechnology-enabled plant agriculture, as the processes between nanoparticles and root interfaces such as root compartments and root exudates remain largely unclear. Here, using iron deficiency–induced plant chlorosis as an indicator phenotype, we evaluated the iron transport capacity of Fe 3 O 4 nanoparticles coated with citrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Based on these findings, we posit that MgFe-LDHs or other LDHs containing Fe(II) and Fe(III) have the potential to become a new generation of iron fertilizers, serving as a supplement to chelated iron. MgFe-LDHs present unique advantages in iron supplementation strategies compared to other traditional methods: (i) they boast broad applicability, potentially accommodating various soil types; (ii) unlike many other iron-containing nanomaterials, MgFe-LDHs exhibit the ability to selectively adsorb onto plant root hairs, a trait seldom reported for other iron nanomaterials [ 13 ]; and (iii) whereas increased iron content often inhibits growth in certain biological iron supplementation methods [ 2 , 3 ], no such growth inhibition was observed in the present study. Moreover, due to their ease of synthesis and low cost, these materials could be widely used in developing countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, we posit that MgFe-LDHs or other LDHs containing Fe(II) and Fe(III) have the potential to become a new generation of iron fertilizers, serving as a supplement to chelated iron. MgFe-LDHs present unique advantages in iron supplementation strategies compared to other traditional methods: (i) they boast broad applicability, potentially accommodating various soil types; (ii) unlike many other iron-containing nanomaterials, MgFe-LDHs exhibit the ability to selectively adsorb onto plant root hairs, a trait seldom reported for other iron nanomaterials [ 13 ]; and (iii) whereas increased iron content often inhibits growth in certain biological iron supplementation methods [ 2 , 3 ], no such growth inhibition was observed in the present study. Moreover, due to their ease of synthesis and low cost, these materials could be widely used in developing countries.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Yu et al reported that FeO NP fertilization could significantly increase rice ( Oryza sativa L.) yield by regulating the activities of enzymes and enhancing nitrogen fixation, but they did not focus on the accumulation of iron in plants [ 12 ]. Additionally, the use of Fe 3 O 4 nanoparticles coated with citrate (CA) or polyacrylic acid (PAA) to combat Fe deficiency in plants has been explored [ 13 ]. However, these fertilizers cannot replace chelated iron, and the development of green, efficient, and inexpensive new Fe fertilizers is still the key to solving the problem of plant trace element deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…26 Although the significant potential of Fe NMs has been documented under laboratory conditions, studies of foliar application in the field are scarce. 24,27,28…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite the huge potential of this technology, the current investigations of nano-enabled sustainable agriculture mainly focused on commercial crops and short-term studies (i.e., less than one year) [23][24][25] , and almost nothing is known about the long-term in uence of FeONPs on globally distributed crops (e.g., rice) subjected to important GHG emissions and fertilization pressure. Developing the next generation of fertilizers is critical if we are up to continue feeding a growing human population while mitigating climate change.…”
Section: Introductionmentioning
confidence: 99%